Universities as Community Partners In an Age of Political Discontent - Matthew R. Auer (Transylvanian Review of Administrative Sciences, 2024)
This essay considers the positioning of universities as community partners amid uncertain—and for many—unsettling political times. An argument is made for universities to reflect on contemporary trends and to orient their missions to these trends. Inevitably, this work requires universities to think clearly and decisively about ‘what they are good at’ vis-à-vis the needs of the community—regardless of how communities are defined. Universities already advance different stakeholders’ core aims and values. But even deeper engagement is needed as popular allegiance to democracy shows signs of wear. Distinctive strengths of universities as providers of public goods are considered. The need to step-up community partnerships, as a value-maximization strategy, is highlighted. The question of how partnerships relate to the long-term survival of universities is contemplated.